Exploring the opportunities and risks of aerial monitoring for biodiversity conservation - Millner, Naomi; Cunliffe, Andrew M.; Mulero-Pázmány, Margarita Cristina; Newport, Ben; Sandbrook, Chris; Wich, Serge A. (Bristol University Press, 2023)
Drones are unoccupied aerial systems (UAS) whose technology has evolved rapidly over the past 15 years. Increasingly used in conservation to manage and monitor biodiversity, drones offer rich capabilities to observe in difficult terrain, have relatively affordable hardware costs and are likely to continue to proliferate rapidly in the years ahead. Drones are useful for tasks as diverse as monitoring wildlife poaching and illegal timber extraction, managing ecotourism and disaster responses, and tracking the regeneration or degradation of forests, and offer potential for more specialised tasks as their sensory payloads are developed. However, although associated technical issues and applications have been explored in wide-ranging ways within conservation science, there has been relatively little social-scientific engagement with drones to date. This leaves a gap surrounding the potential social benefits and risks of drones, as well as in interdisciplinary conversations. This introduction is the first of four papers under the heading ‘Drone ecologies’, building on an interdisciplinary workshop held under the same name at the University of Bristol in July 2021. Expanding from the plenary dialogues that opened this workshop, this introduction explores what interdisciplinary perspectives on drones can offer in addressing global social and ecological challenges, drawing on expertise from the fields of conservation biology, human and physical geography, rainforest ecology and environmental systems. Setting out the aims of the overall special collection, we review here the ways that drones are being used, and might be used, in biodiversity conservation, setting out important considerations to minimise risks of inadvertent harms.
Keywords: Biodiversidad - Conservación - Innovaciones tecnológicas; Drones; Biodiversity